Reactivity of a Cadmium–Terpyridine Complex: [Cd(L1)(NO3)2(H2O)] (L1 = (4′-(4-bromophenyl)-2,2′:6′,2″-terpyridine) - Lee, Gang Min; Yoon, Woojin; Yun, Hoseop; Lee, Soon W. (Bulletin of the Korean Chemical Society, 2021)
A novel pincer-type ligand L2 (4′-(4-(6-methoxypyridin-3-yl)phenyl)-2,2′:6′,2″-terpyridine), a terpyridine derivative, was prepared by Suzuki–Miyaura C-C coupling. Under heating conditions in ethanol, ligands L1 (4′-(4-bromophenyl)-2,2′:6′,2″-terpyridine) and L2 reacted with Cd(NO3)2·4H2O to produce [Cd(L1)(NO3)2(H2O)] (1) and [Cd(L2)(NO3)2(H2O)]·(H2O) (2), respectively. In complexes 1 and 2, the seven-coordinate cadmium metal is coordinated to one terpyridine ligand, two nitrato ligands, and an aqua ligand. Under heating conditions in acetonitrile at 120-°C, complex 1 was converted into a 1:1 mixture (3) of [Cd2L2(NO3-κ3O,O′,O″)(NO3-κ2O,O′)3] (3a) and [CdL(NO3-κ2O,O′)2] (3b). When complex 1 was treated with 4,4′-bipyridine (bpy) under hydrothermal conditions, a one-dimensional linear coordination polymer [[Cd(L1)(bpy)(NO3)](NO3)(H2O)2]∞ (4) was produced. Complex 1 reacted with 4-((E)-2-(pyridin-4-yl)vinyl)pyridine (bpe) in ethanol under microwave-heating conditions to produce a dimeric complex [Cd2(L1)2(bpe)(EtOH)2(NO3)2)]·(NO3)2 (5). Solid-state photoluminescent spectra of all complexes displayed a ligand-based π–π* emission band.
Keywords: Coordination Polymers; Dimeric complexes; Emission bands; Heating conditions; Hydrothermal conditions; Nitrato ligands; Photoluminescent spectra; Pincer-type ligand; Cadmium; Coordination polymer; Photoluminescence; Terpyridine derivatives